New reddish species of Moenkhausia Eigenmann (Characiformes: Characidae) from the upper rio Xingu basin, Brazil - Reia, Lais [UNESP]; E Silva, Gabriel de Souza Costa [UNESP]; Oliveira, Claudio [UNESP]; Benine, Ricardo Cardoso [UNESP] (My University, 2024)
A new species of Moenkhausia from the rio Culuene, rio Xingu basin, in Mato Grosso State is described here through genetic and morphological data. This new species differs from all congeners by the following combination of characters: the presence of reddish color on the posterior portion of the body, as well as on the base of anal, adipose, and pelvic fins in live specimens; a conspicuous midlateral dark stripe, which extends from posterior margin of opercle to the middle of caudal-fin rays, becoming wider and more conspicuous from the vertical through the dorsal-fin origin; absence of humeral blotch; absence of blotches on caudal-fin lobes; by having the concentration of dark pigments on the anterior margin of the caudal-fin rays; and presence of 2–3 maxillary teeth. A brief discussion about its putative relationships with other congeners is presented.
Keywords: Amazon basin; Mitochondrial DNA; Moenkhausia lopesi; Taxonomy; Tetra